2014
DOI: 10.1021/jp504004e
|View full text |Cite
|
Sign up to set email alerts
|

Nature of Tunable Optical Reflectivity of Rocksalt Hafnium Nitride Films

Abstract: Although the phenomenon that optical reflectivity of hard group IVB transition metal nitrides depends on stoichiometry has been reported, the microscopic origin of this behavior has not been well explored yet. Here we find that optical reflectivity of rocksalt hafnium nitride films (δ-HfN x ) can be effectively tuned by stoichiometry x, and the underlying mechanism can be well elucidated by Drude−Lorentz fitting and first-principles calculations. It is shown that the observed tunability of optical reflectivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…Three metallic Hf-vacancy nitrides, including P1-Hf 11 N 12 , P1-Hf 7 N 8 and C 2/m-Hf 4 N 5 are stable at 0 GPa, consistent with the stoichiometries proposed by experiments of Hf-vacancies containing in HfN x film (x > 1) [9,10]. The ground-state phase we find for Hf 3 N 4 is not the orthorhombic Zr 3 N 4 -type (Pnma) which was proposed [15,19] (Fig.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…Three metallic Hf-vacancy nitrides, including P1-Hf 11 N 12 , P1-Hf 7 N 8 and C 2/m-Hf 4 N 5 are stable at 0 GPa, consistent with the stoichiometries proposed by experiments of Hf-vacancies containing in HfN x film (x > 1) [9,10]. The ground-state phase we find for Hf 3 N 4 is not the orthorhombic Zr 3 N 4 -type (Pnma) which was proposed [15,19] (Fig.…”
supporting
confidence: 85%
“…Among them, hafnium nitrides (HfN x ), display high melting points (HfN: 3330 ℃ [1]), high incompressibility (HfN: B 0 =260-306 GPa [2]; Hf 3 N 4 : B 0 = 227-260 GPa [3,4]), oxidation resistance at high temperature [5] and superconductivity (HfN: T c =8.8 K) [6], and have been widely exploited by experiments [7][8][9][10] and calculations [8][9][10][11] in recent years.…”
mentioning
confidence: 99%
“…HfN x predominantly exists in two crystal phases: highly resistive Hf 3 N 4 with Hf(IV) oxidation state [9,10], and low resistivity δ-HfN with Hf(III) oxidation state [11,12]. The control of the oxidation state of Hf is therefore essential to synthesize conductive HfN x layers [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The control of the oxidation state of Hf is therefore essential to synthesize conductive HfN x layers [13][14][15]. Physical vapor deposition (PVD) methods have been widely adopted for the synthesis of low resistivity HfN x films [8,11,12,[16][17][18][19]. Seo et al have reported the growth of stoichiometric and epitaxial 500 nm thick HfN x layers with a resistivity of 1.4 × 10 -5 Ωcm, which is the lowest resistivity value reported thus far [18].…”
Section: Introductionmentioning
confidence: 99%
“…Two envisioned applications are the combination of HfO 2 with HfN as gate dielectric and gate metal in a MOS configuration as reported by Yu et al 1,5 and HfN as back reflector electrode for copper-indium-gallium-selenide solar cells, due to its high reflectivity (>85%) in the low energy photon region (1 eV E 2.4 eV) for semi-infinite films. [6][7][8] Both applications require low resistivity of HfN layers (q ¼ 10…”
Section: Introductionmentioning
confidence: 99%